2017
DOI: 10.1109/tsp.2016.2637317
|View full text |Cite
|
Sign up to set email alerts
|

Parallel and Distributed Methods for Constrained Nonconvex Optimization—Part I: Theory

Abstract: Abstract-In Part I of this paper, we proposed and analyzed a novel algorithmic framework for the minimization of a nonconvex (smooth) objective function, subject to nonconvex constraints, based on inner convex approximations. This Part II is devoted to the application of the framework to some resource allocation problems in communication networks. In particular, we consider two non-trivial case-study applications, namely: (generalizations of) i) the rate profile maximization in MIMO interference broadcast netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
317
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(317 citation statements)
references
References 51 publications
0
317
0
Order By: Relevance
“…The constraint (8a) is an under-estimator for γ k,n and b k,n in (8b) is a over-estimator for the total interference seen by user k on subchannel n. Even after relaxing (2) with (8), the resulting problem is not convex due to the constraints (8a) and (7f). Therefore, we adopt successive convex approximation (SCA) method in [13], [14], where the nonconvex constraints are replaced by a sequence of convex subsets that can be solved iteratively until convergence.…”
Section: Beamformer Design With Fixed Quantization Levelmentioning
confidence: 99%
“…The constraint (8a) is an under-estimator for γ k,n and b k,n in (8b) is a over-estimator for the total interference seen by user k on subchannel n. Even after relaxing (2) with (8), the resulting problem is not convex due to the constraints (8a) and (7f). Therefore, we adopt successive convex approximation (SCA) method in [13], [14], where the nonconvex constraints are replaced by a sequence of convex subsets that can be solved iteratively until convergence.…”
Section: Beamformer Design With Fixed Quantization Levelmentioning
confidence: 99%
“…Until recently, there are some references designing algorithms for distributed nonconvex problems, such as [16,17]. In [16], Lorenzo and Scutari developed a novel distributed algorithm for solving unconstrained nonconvex optimization problems which associated a multiagent network with timevarying connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…They combined a successive convex approximation technique and a dynamic consensus mechanism to realize distributed computation as well as local information exchange in the network. For nonconvex optimization problems with constraints, Scutari et al [17] proposed a successive convex approximation method by solving a sequence of strongly convex subproblems while maintaining feasibility. They have shown that their proposed method can converge to a stationary solution of the original constrained nonconvex problem under consideration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations